Angiogenesis-related cytokines in serum of proliferative diabetic retinopathy patients before and after vitrectomy - Li, Shuang; Fu, Xun-An; Zhou, Xiao-Fang; Chen, You-Yan; Chen, Wei-Qun (International journal of ophthalmology, 2012)
AIM: To evaluate serum concentrations of angiogenesis- related cytokines in proliferative diabetic retinopathy (PDR) before and after vitrectomy. METHODS: Serum samples were collected from 30 PDR patients with varying severity before and after vitrectomy. Serum concentrations of vascular endothelial growth factor (VEGF), pigment epithelium-derived factor (PEDF), interleukin-8 (IL-8) and interferon-inducible protein-10 (IP-10) were determined by enzyme-linked immunosorbent assays(ELISA). RESULTS: Serum concentrations of VEGF, PEDF, IL-8 and IP-10 were significantly higher in PDR patients than that in controls, respectively (P <0.05). VEGF concentration decreased significantly in postoperative samples than that in preoperative samples (P <0.05). The concentrations of PEDF, IL-8 and IP-10 did not exhibit significant changes after vitrectomy. CONCLUSION: Elevated cytokines levels in serum may be diagnostically useful in PDR. Angiogenesis-related cytokines play important roles in the development of PDR, and would instruct the risk assessment of pathogenetic condition in PDR patients.